2014
DOI: 10.1590/jvb.2014.005
|View full text |Cite
|
Sign up to set email alerts
|

Long-term clinical and ultrasonographic evaluation of thrombophilic patients with deep venous thrombosis

Abstract: Objective: The purpose of this study was to evaluate the long term clinical and ultrasonographic outcomes of thrombophilic patients with deep venous thrombosis (DVT). Method: Cohort study, retrospective case-control with cross-sectional analysis. Thirty-nine thrombophilic patients and 25 non-thrombophilic patients were assessed 76.3 ± 45.8 months after diagnosis. Demographic and family data were collected, as well as data from clinical and therapeutic progress, and physical and ultrasound examinations of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
1
1
Order By: Relevance
“…Assessing adequacy of suture properties, a previous study reported that the force in the human flexor digitorum profundus and flexor digitorum superficialis tendons ranged 2–9 N during active extension and passive flexion and 2–19 N during active unresisted flexion, indicating that the tensile strength of the 2–0 barbed PVDF sutures (22.4 N) is more appropriate than the tensile strength of 2–0 barbed PP sutures (14.0 N) 33 . A previous study of only PP 2–0 barbed sutures reported an ultimate tensile force of 40 N, which was higher than the 14 N in our study 34 . This discrepancy can likely be explained by different barb cutting parameters, as our previous work showed that the peak tensile force decreased from 33 to 26 N when the cut depth increased from 0.07 to 0.18 mm with a constant cut angle of 160° 4,20 …”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Assessing adequacy of suture properties, a previous study reported that the force in the human flexor digitorum profundus and flexor digitorum superficialis tendons ranged 2–9 N during active extension and passive flexion and 2–19 N during active unresisted flexion, indicating that the tensile strength of the 2–0 barbed PVDF sutures (22.4 N) is more appropriate than the tensile strength of 2–0 barbed PP sutures (14.0 N) 33 . A previous study of only PP 2–0 barbed sutures reported an ultimate tensile force of 40 N, which was higher than the 14 N in our study 34 . This discrepancy can likely be explained by different barb cutting parameters, as our previous work showed that the peak tensile force decreased from 33 to 26 N when the cut depth increased from 0.07 to 0.18 mm with a constant cut angle of 160° 4,20 …”
Section: Discussioncontrasting
confidence: 59%
“…33 A previous study of only PP 2-0 barbed sutures reported an ultimate tensile force of 40 N, which was higher than the 14 N in our study. 34 This discrepancy can likely be explained by different barb cutting parameters, as our previous work showed that the peak tensile force decreased from 33 to 26 N when the cut depth increased from 0.07 to 0.18 mm with a constant cut angle of 160 . 4,20 The strength of a tendon repair is governed by several factors, including, but not limited to, the configuration or suture pattern, number of strands crossing the repair, tensile strength of the suture, and suture pullout force, an indicator of the suture anchoring performance.…”
Section: Discussionmentioning
confidence: 93%